PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) DI SEKOLAH DASAR - Kasmawati, Enita (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research background by learning IPS observations are not attractive and interactive for the students. Therefore, action is taken by using cooperative learning model type Group Investigation (GI) aims to improve the learning process in order to enhance social studies learning outcomes IPS in class IV. The average assessment of learning design first cycle was 75.1% up on the second cycle to 92.9%. Assessment of the implementation aspects of the teacher's first cycle was 75.1% up on the second cycle to 93.8%, and the aspects of students' first cycle was 75% increase in cycle II to 90.6%. As well as student learning outcomes in the first cycle was 73.2 rising to 83.2 in the second cycle. Thus it can be said that the GI type cooperative learning model to improve student learning outcomes in learning social studies in class IV SDN 11 Sungai Aur District of  Pasaman Barat. Kata kunci: peningkatan; hasil belajar IPS; model; kooperatif gi.